Contributions of Biomass Burning and Other Sources to Fine Particle Level and Oxidative Potential in Suburban Tokyo, Japan - Akihiro Fushimi; Ana M. Villalobos; Akinori Takami; Kiyoshi Tanabe; James J. Schauer (Aerosol and Air Quality Research)
Abstract Fine particulate matter (PM2.5) in the atmosphere is of high priority for air quality management efforts due to well-established associations with adverse effects on human populations. To develop effective countermeasures against PM2.5 emission sources, its origin needs to be efficiently characterized. Atmospheric PM2.5 samples were collected from a suburban Tokyo city, Tsukuba, Japan in 2012–2013 to estimate source contributions, with a focus on biomass open burning. The particulate mass, elemental carbon, organic carbon (OC), water-soluble organic carbon, inorganic ionic species, elements, organic markers, and biological oxidative potentials were measured using the PM2.5 samples. Results showed remarkably high levoglucosan concentrations in fall, suggesting enhanced open burning contributions during this season. The analysis of levoglucosan/β-sitosterol ratios suggested that levoglucosan is still a good marker of biomass burning; however, it may be useful to use β-sitosterol in combination with levoglucosan or as a supplement. Major emission sources and their contributions to the annual average OC concentrations were estimated to be secondary organic aerosols (SOA, 31.9%), vehicle exhausts (22.2%), open burning (8.4%), and cooking (5.1%). The estimated relative contribution of open burning to OC concentrations was highest in November (20.4%) and lowest in June (3.3%). The PM2.5 oxidative potentials were highest in spring and summer. Correlation and meteorological analyses suggest that emissions from ships (or other residual oil combustion) and anthropogenic SOA originating from the Tokyo Metropolitan Area, and biogenic SOA contribute to an increase in PM2.5 oxidative potential during the warm season in the suburbs of Tokyo. Neither open burning nor vehicle exhaust source contributions showed a strong positive correlation with the PM2.5 oxidative potential.